A exclusão escolar e o Instituto Federal de São Paulo, Campus Bragança Paulista - Silva, Karla Cristiny Moraes da (Universidade Federal de São Carlos, 2019)
The present study has as object of study the school dropout of the Federal Institute of Education, Science and Technology of São Paulo (IFSP), Campus Bragança Paulista. Understanding it as synonymous with school exclusion, we analyze its determinants based on Bourdieu's sociology, seeking to understand how the social positions of former students influenced their school trajectories, making them longer or shorter, completion or exclusion. The data collection involved three steps: (i) collection of secondary data in the academic systems of the Federal Institute; (ii) application of a survey survey; and (iii) semi-structured interviews. In the first one, we identified that the dropout / exclusion rates of the courses in the institution reach 69% (Bachelors in Mathematics). The data collected comprise a total of 8 years of activities (from the first half of 2009 to the second half of 2017). The data of the survey were interpreted through the Multiple Correspondence Analysis (LEBARON, 2009). This analysis showed that the excluded were, mostly, from popular social groups. We also selected graduated and non-formed alumni for interviews, generating a new database with which we used the technique of content analysis (BARDIN, 2011). We observed that the decision-making of these individuals on whether or not to complete the studies in the institution was delimited by their social origins. Among those excluded, we realized that, because of their properties, they did not feel they belonged to the school space. On the other hand, even among the poorest individuals, an organized family and the encouragement of parents to study, they differed for the students, as well as the support of classmates, teachers and institutional programs (monitoring and student aid). In this way, the research represents a contribution to the IFSP-BRA, by redefining the profile of its target audience, which will allow future studies to reflect on possible strategies to combat the exclusion of its courses.
The school exclusion and the Federal Institute of São Paulo, Campus Bragança Paulista
Keywords: Evasão escolar; Exclusão escolar; Instituto Federal de São Paulo (Campus Bragança Paulista); Bourdieu, Pierre, 1930-2002; School dropout; School exclusion; CIENCIAS HUMANAS::EDUCACAO::ADMINISTRACAO EDUCACIONAL; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS